Correlation between Physical Activity, Muscle Mass, Body Fat, and Biological Age - Mely Juwita Limbong; Yunus Elon (GLOBAL HEALTH SCIENCE GROUP, 2024)
Physical activity plays a crucial role in maintaining a healthy and balanced body, particularly in relation to body composition, including muscle mass, body fat percentage, and biological age. This study aims to analyze the relationship between physical activity levels and muscle mass, body fat and biological age within the population of Cihanjuang Rahayu Village. This research employed an observational design with a cross-sectional approach. Data collection was conducted using the Global Physical Activity Questionnaire (GPAQ), a bioimpedance device (BIO Omron), and height measurements. The Chi-Square test was utilized for data analysis to assess the relationships between the variables. The total population for the study consisted of 242 individuals, based on predetermined inclusion and exclusion criteria. A sample of 151 respondents was selected using the Slovin formula with a 5% margin of error. Based on the physical activity scores from the population of Cihanjuang Rahayu Village, the highest score was from learning/working activities, with an average value of 4.89. The distribution of muscle mass among the community members showed that 59.6% fell into the moderate category, with muscle mass ranging from 19.9 to 29.7 kg. Regarding body fat, 36.4% of the community was categorized as having healthy body fat. The biological age of the community members was mostly in the early elderly category, representing 33.1% of respondents. From the Chi-Square test, the relationships between physical activity and muscle mass (p-value > 0,05), physical activity and body fat (p-value > 0,05), and physical activity and biological age (p-value > 0.05) showed no significant associations between physical activity and these body components. Although there was no significant relationship found between physical activity and muscle mass, body fat, or biological age, physical activity still plays a vital role in promoting overall health and well-being.